2020
DOI: 10.35706/eltinfc.v2i2.3054
|View full text |Cite
|
Sign up to set email alerts
|

Providing teaching resources for young learner classes: Best practices in efl context

Abstract: The availability of teaching resources is one of important factors to create successful lessons in teaching English to young learners (TEYL). Teachers can use flashcards, toys, songs, rhymes, books, audio visual materials, digital recourses and others to support teaching and learning process. Ready-made materials are available in stores, however they are usually expensive. The aim of this article is to share one of the best practices in providing resources for young learners in learning English. In the academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Regarding classroom management-related challenges, large class sizes and their time-consuming nature, and students' poor English competence and a wide language proficiency gap among them have been stated as major domains. Early works acknowledge teachers face large class sizes and their time-consuming nature (Khadka, 2019;Loiacono & Allen, 2008;Simanova, 2010), poor English competence, and a wide language proficiency gap among students (Reyes & Rodriguez, 2005;Syathroh, Musthafa & Purnawarman, 2019;Valentic, 2005) in MAC. Understanding and paying equal attention to all the students might be a challenge for MACs teachers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding classroom management-related challenges, large class sizes and their time-consuming nature, and students' poor English competence and a wide language proficiency gap among them have been stated as major domains. Early works acknowledge teachers face large class sizes and their time-consuming nature (Khadka, 2019;Loiacono & Allen, 2008;Simanova, 2010), poor English competence, and a wide language proficiency gap among students (Reyes & Rodriguez, 2005;Syathroh, Musthafa & Purnawarman, 2019;Valentic, 2005) in MAC. Understanding and paying equal attention to all the students might be a challenge for MACs teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies indicated it is difficult to know all students, and every difference of them and devote to address all equally (Simanova, 2010;Syathroh, Musthafa & Purnawarman, 2019;Ur, 2005), it may not be rational to teach focusing on one group of students. If the teachers plan lessons and teach to the middle on average students' level ignoring the majority of low achievers and/or some high achievers, the instructions failed to address the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ratminingsih et al (2018) found out that EYL teachers were interested in using ICT and would like to use the ICT when they were planning their lessons and when they were teaching in class. Moreover, for those who do not get access to technology, Syathroh et al (2019) proposed some resources for TEYL to teach different skills that can be created by the EYL teachers. Using papers and crafts materials the teacher can involve the young learners to make the media.…”
Section: Introductionmentioning
confidence: 99%